Fairness and motivation - Armin Falk (IZA World of Labor, 2014)
How do firms motivate their employees to be productive? The conventional wisdom is that workers respond to monetary incentives—"Pay them more and they will work harder." However, a large and growing body of empirical evidence from laboratory and field experiments, surveys, and observational data, as well as neuroeconomic research, suggests that workers' perceptions of fairness and trust are also key drivers of their work effort. Treating employees with respect is not only ethically warranted, it can create positive economic outcomes for both the worker and the firm.
Keywords: C7; D63; D82; H41; C9; J3; 330; fairness; wages; effort; reciprocity; backfiring incentives